1994
DOI: 10.1016/0014-5793(94)01218-0
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of sphingosine in induction of apoptosis by tumor necrosis factor‐α, in human neutrophils

Abstract: Abstnset Treatment of human neutrophils with tumor necrosis factor-a (I'NF-u) resulted in an increase in concentration of ceramide and its catabolite, sphingosine. Sphingosine, a potent endogenous protein kinase C (PKC) inhibitor, as well as TNF-a, induced intemucleosomal DNA fragmentation and morphological changes characteristic of apoptotic cells. &amide and sphingosine-l-phosphate, the initial product of sphingosine catabolism. did not cause anontosis under our experimental conditions. In addition, 1-(5isoq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 28 publications
6
134
1
Order By: Relevance
“…Ͻ 30 min) of TNF-␣-induced contractile dysfunction in isolated cardiac myocytes (6), thin strips of isolated muscle (8), as well as in the intact left ventricle (6). Both the time course and absolute values for the TNF-␣-induced increase in free sphingosine levels in intact myocytes are consistent with previously reported values for sphingosine levels obtained from whole cell lipid extracts following TNF-␣ stimulation (40). A second important point shown by Fig.…”
Section: Resultssupporting
confidence: 88%
“…Ͻ 30 min) of TNF-␣-induced contractile dysfunction in isolated cardiac myocytes (6), thin strips of isolated muscle (8), as well as in the intact left ventricle (6). Both the time course and absolute values for the TNF-␣-induced increase in free sphingosine levels in intact myocytes are consistent with previously reported values for sphingosine levels obtained from whole cell lipid extracts following TNF-␣ stimulation (40). A second important point shown by Fig.…”
Section: Resultssupporting
confidence: 88%
“…Although our results show that the apoptosis-inducing action is not specific to sphingosine, and may extend to -erythrosphingosine or stearylamine, a functional role for this sphingolipid in mediating apoptotic signals from different external insults cannot be excluded. Previous studies have demonstrated that sphingosine is an endogenous modulator that mediates apoptotic signals induced by TNFα in neutrophils and cardic myocytes [44,45]. It has also been reported that sphingosine can markedly potentiate the induction of apoptosis by ceramide when present at submicromolar levels, which may also have physiological significance [46].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, SAHA treatment activated JNK, albeit modestly, and associated lethal e ects were partially attenuated by interference with c-Jun transactivation of AP-1. In view of evidence that (1) an intact SAPK-JNK/AP-1 axis is required for the lethal actions of ceramide (Verheij et al, 1996), and (2) perturbations in ceramide and sphingosine metabolism accompany leukemic cell maturation and apoptosis (Ohta et al, 1995), such ®ndings raise the possibility that these lipid messengers may be involved in SAHA-induced apoptosis. Studies designed to test this hypothesis are underway.…”
Section: Discussionmentioning
confidence: 99%